2002
DOI: 10.1128/iai.70.10.5676-5683.2002
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Metalloprotease Gene Family of Microsporum canis

Abstract: Keratinolytic proteases secreted by dermatophytes are likely to be virulence-related factors. Microsporum canis, the main agent of dermatophytosis in dogs and cats, causes a zoonosis that is frequently reported. Using Aspergillus fumigatus metalloprotease genomic sequence (MEP) as a probe, three genes (MEP1, MEP2, and MEP3) were isolated from an M. canis genomic library. They presented a quite-high percentage of identity with both A. fumigatus MEP and Aspergillus oryzae neutral protease I genes. At the amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
77
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 50 publications
0
77
0
1
Order By: Relevance
“…For this reason, the secretion of a great variety of enzymes by dermatophytes, such as proteases, lipases, elastases, collagenases, phosphatases and esterases, is one of the most important factors during the infectious process. 15,19,20 This enzymatic machinery is one of the best-characterized virulence factors of dermatophytes, allowing the hydrolisis of structural components of the epidermal tissue and the invasive character of these pathogens. Among the wide variety of enzymes secreted by dermatophytes, proteolytic enzymes are the most studied, and the importance of keratinolytic proteases to the pathogenicity is well established.…”
Section: Host-dermatophyte Interaction and The Pathogenesis Of Dermatmentioning
confidence: 99%
“…For this reason, the secretion of a great variety of enzymes by dermatophytes, such as proteases, lipases, elastases, collagenases, phosphatases and esterases, is one of the most important factors during the infectious process. 15,19,20 This enzymatic machinery is one of the best-characterized virulence factors of dermatophytes, allowing the hydrolisis of structural components of the epidermal tissue and the invasive character of these pathogens. Among the wide variety of enzymes secreted by dermatophytes, proteolytic enzymes are the most studied, and the importance of keratinolytic proteases to the pathogenicity is well established.…”
Section: Host-dermatophyte Interaction and The Pathogenesis Of Dermatmentioning
confidence: 99%
“…M36 metallopeptidases (also known as fungalysins) are known to promote fungal pathogenicity both in animals and in plants. 19,20,21,22 We identified all members of this protein family in the T. calospora genome and assessed their expression in S. vomeracea mycorrhizal protocorms. Ten genes coding for putative fungalysins (Table 1) were found, that clustered in different phylogenetic groups inside this family (Fig.…”
mentioning
confidence: 99%
“…Aspergillus fumigatus, Coccidioides immitis, Cryptococcus neoformans, Microsporum canis, dermatophytic fungi), where they help fungi during host tissue invasion either because they degrade structural components of the host extracellular matrix, 19,20 or because they degrade immunodominant cell surface antigens, thus escaping host recognition. 23 This gene family has expanded in the Onygenales, that includes several animal pathogens, 24 with a rapid functional divergence of the duplicated proteins.…”
mentioning
confidence: 99%
“…The purified protein was then shown to degrade the structural protein elastin, which is a component of human lungs, suggesting that fungalysins promote pathogenicity by degrading extracellular matrix proteins. This model was strengthened by the observation that a fungalysin from Microsporum canis, which causes skin diseases in cats and dogs, is able to degrade the structural protein keratin (4). Besides these examples, few protein-based studies of fungalysin proteins or their substrates have been reported.…”
mentioning
confidence: 99%